Teaching recent global history dialogues among historians, social studies teachers, and students (Transforming teaching, 2014)
"Teaching Recent Global History explores innovative ways to teach world history, beginning with the early 20th century. The authors' unique approach unites historians, social studies teachers, and educational curriculum specialists to offer historically rich, pedagogically innovative, and academically rigorous lessons that help students connect with and deeply understand key events and trends in recent global history. Highlighting the best scholarship for each major continent, the text explores the ways that this scholarship can be adapted by teachers in the classroom in order to engage and inspire students. Each of the eight main chapters highlights a particularly important event or theme, which is then complemented by a detailed discussion of a particular methodological approach. Key features include: An overarching narrative that helps readers address historical arguments; Relevant primary documents or artifacts, plus a discussion of a particular historical method well-suited to teaching about them; Lesson plans suitable for both middle and secondary level classrooms; Document-based questions and short bibliographies for further research on the topic.This invaluable book is ideal for any aspiring or current teacher who wants to think critically about how to teach world history and make historical discussions come alive for students"--Provided by publisher.